Cat treats : - Anderson, Janice (Hamlyn, 2002)
Cat lovers are famous for pampering their feline friends. These fury creatures eat the best food, wear the most fashionable collars, and enjoy the best toys. Let's face it: most cats rule their owners, so when they turn up their noses at their food, what are we supposed to do? Start cooking!